The Effect of Residential Re- Subdivision - Abbas, Sana Sati; Mohammed, Farah Gazi (Iraqi Journal of Architecture and Planning, 2018)
This paper studies the concept of residential land re-subdivision, and the role of regulations, instructions and standards in organizing this process, to provide residential plots which are suitable in their dimensions and areas to the residence. Residential re-subdivision affected by many factors such as number of new households, their economic situation, and the plot areas; which enable the families to adopt this solution The residential land re-subdivision is a good solution to reduce shortage in housing stock, and minimizing the pressure on the residential demand , but at the same time it is a reason for increasing the accommodation and population densities and the floor area ratio ( F.A.R) ,as well as increasing the demand on the social and technical infrastructure . The aim of this papers is to build a theoretical framework to the residential land re-subdivision, determined the factors that affect on it, and its effects on the residential area. The research problem is that, "residential re-subdivision effects on planning standards of the plots and residential areas ", while the research hypothesis is that," the residential re- subdivision produced new planning standards which have negative effects on the plots in residential areasâ€. The research finding was that the residential re-subdivision was a main reason for reducing the housing shortage, getting the new household a private residential space, at the same time; it was the reason for raising the population, accommodation densities, and the floor area ratio. Also the paper found that the residential re-subdivision has been according to the household need, and according to the space left from the residential plot, without adherence to planning and standards related to residential land subdivision ,this was the reason for the appearance of plots of different areas and dimensions ,and some times of very small areas .